PERANAN TEKNOLOGI INFORMASI DAN KOMPUTER BERBASIS WEB PADA PENINGKATAN KEMAMPUAN BELAJAR SISWA SMK NEGERI DI BATAM - Hendi Sama (Universitas Putera Batam, 2013)
Judging from the development of various educational institutions in Indonesia, we can see that the province of Riau Islands and Batam in particular, already has a wide selection of quality educational institutions, and can produce graduates who are skilled and efficient. On the role of secondary schools as an educational institution is very important, especially from the age limit teenagers who are usually in the upper secondary education level. This role is supported by a variety of facilities received from the government, including information technology support. This research attempts to carry out a research on how to apply, act and socialize using web-based technology and powerful computers for the community, especially the increase in learning ability of students in vocational schools in Batam. From the results of this study found that students' ability to learn further increased by the application of information technology and web-based computer is good and right. School management and teachers welcomed very well and expect to further research to be carried out each year to their students.